β Property in Orlicz Sequence Spaces Equipped with s-norm - CUI Yun-an; DONG Jia-qi (Journal of Harbin University of Science and Technology)
Orlicz spaces equipped with s-norm is an extension of Orlicz spaces. In order to studing the H property and the property β in Orlicz space equipped with s-norm，some basic properties of the s-norm are discussed firstly. Then, based on this, Φ∈δ2which is the criteria of H property of Orlicz sequence spaces equipped with s-norm were given. In this paper, we get that the Orlicz sequence space equipped with s-norm have property β if and only if the spaces is reflexive，that is Φ∈δ2∩δ'2.